2017
DOI: 10.1038/cddis.2017.200
|View full text |Cite
|
Sign up to set email alerts
|

NMI inhibits cancer stem cell traits by downregulating hTERT in breast cancer

Abstract: N-myc and STAT interactor (NMI) has been proved to bind to different transcription factors to regulate a variety of signaling mechanisms including DNA damage, cell cycle and epithelial–mesenchymal transition. However, the role of NMI in the regulation of cancer stem cells (CSCs) remains poorly understood. In this study, we investigated the regulation of NMI on CSCs traits in breast cancer and uncovered the underlying molecular mechanisms. We found that NMI was lowly expressed in breast cancer stem cells (BCSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Our single-cell tracking allowed us to find values that minimize both these factors. The values we calculated for MCF-7 cells conform very closely to what many in the field have chosen to employ ( Choi et al., 2017 , Feng et al., 2017 , Morata-Tarifa et al., 2016 ). T47D spheres proved to be much smaller and slower growing.…”
Section: Discussionsupporting
confidence: 66%
“…Our single-cell tracking allowed us to find values that minimize both these factors. The values we calculated for MCF-7 cells conform very closely to what many in the field have chosen to employ ( Choi et al., 2017 , Feng et al., 2017 , Morata-Tarifa et al., 2016 ). T47D spheres proved to be much smaller and slower growing.…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies have found that hTERT does not depend on its telomere-lengthening function or its telomerase activity to promote cancer cell growth and metastasis. [43] Liu et al [44] reported that hTERT interacts with β-catenin and promotes the epithelial–mesenchymal transition and stem cell-like traits in cancer cells. Hu et al demonstrated that the hTERT-MDM2 complex enhances ITGB1 expression and ultimately promotes cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nmi impacts multiple signaling pathways in a context-dependent manner [ 3 , 20 ]. In particular, recent work from Zhao et al shows divergent results in hepatocellular carcinoma where knockdown of Nmi may inhibit pulmonary metastasis, an interesting observation that highlights the cell and tumor type-specific role of Nmi in cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%